Distribution and Dynamic Behaviors of Landslide in Rangun Khola Watershed of the Western Nepal - Pathak, Lalit; Devkota, Krishna Chandra (Journal of Environment Sciences, 2022)
Being a major devastating hazard, the study of landslides in Nepal Himalaya is very essential. For controlling and mitigate measures, understanding the behaviors and distribution of landslides over the temporal and spatial range is indispensable. The current study is carried out in the Rangun Khola watershed of western Nepal which spreads from Mahabharat Range (2,500m) to Dun valley covering an area of 489.39 km2. Polygon-based landslide inventory within the temporal range of 18 years (2003 to 2020 AD) was prepared by using temporal series of Google Earth Pro, Sentinel-2 images, and Landsat images, which were verified during the field visit. The number of landslides and area covered in different spatial units and temporal intervals were analyzed using the Q-GIS. In total, 494 landslides were identified and the area covered by the landslide was 0.47% of the total study area. Landslides in this area are highly dynamic with different activity states and temporal fluctuation. The number of landslides were highest, i.e., 143, in 2005 and the Upper Siwalik region consist of a large number of landslides making them highly prone to landslide events. The presence of thrust and faults was also found to be influencing the landslides and size distribution. The study will be useful for further researches to map susceptibility and hazard and also for policymakers to understand landslide status to reduce the risk.